Long COVID coping and recovery (LCCR): Developing a novel recovery-oriented treatment for veterans with long COVID - Yosef Sokol; Chana Silver; Sofie Glatt; Lakshmi Chennapragada; Sarah Andrusier; Cameron Padgett; Ariana Dichiara; Marianne Goodman (Contemporary Clinical Trials Communications, 2023)
Background: Long COVID has affected 13.5% of Veterans Affairs (VA) Healthcare System users during the first pandemic year. With 700,000+ United States Veterans diagnosed with COVID-19, addressing the impact of Long COVID on this population is crucial. Since empirically-based mental health interventions for Long COVID are lacking, a vital need exists for a tailored recovery-oriented intervention for this population. This study intends to assess the feasibility and acceptability of a novel recovery-oriented intervention, Long COVID Coping and Recovery (LCCR), for Veterans with Long COVID, aiming to support symptom management and quality of life. LCCR is an adaptation of Continuous Identity Cognitive Therapy (CI-CT), a suicide recovery-oriented treatment for Veterans. Methods: In a two-year open-label pilot, three single-arm treatment trials will be conducted with 18 Veterans suffering from Long COVID. Each trial includes 16 weekly 60-min sessions delivered via VA Video Connect (VVC) and/or VA WebEx. Primary objectives include optimizing LCCR for Veterans with Long COVID and assessing the acceptability and feasibility of the intervention, using attendance and retention rates, drop-out statistics, and client satisfaction levels. Additionally, potential benefits of LCCR will be explored by evaluating alterations in quality of life, resilience, mental health status (anxiety, depression, suicide risk/behavior), and personal identity. The protocol has been tailored based on Veterans' needs assessment interviews and stakeholder feedback. Conclusion: If the LCCR intervention proves feasible and acceptable, a manualized version will be created and a randomized controlled trial planned to examine its efficacy in the broader Veteran population.